Analisis Kekerasan Terhadap Anak: Perspektif Hukum Positif dan Perbandingan Fiqh Empat Madzhab - Ahmad Muhammad Mustain Nasoha; Ashfiya Nur Atqiya; Renaldi, Alvito; Asy Syfak Qolbi Maghfur (El-Faqih : Jurnal Pemikiran dan Hukum Islam, 2024)
Child abuse is a serious issue with lasting impacts. While positive law provides legal protections for children, its implementation faces challenges. In Islamic tradition, fiqh from the four major schools of thought—Maliki, Shafi'i, Hanbali, and Hanafi—also offers guidelines for child protection. This study explores the integration between positive law and fiqh to enhance child protection. Using a qualitative, library research method, the research examines whether Indonesian legislation aligns with the views of these schools. The findings reveal both alignments and differences. Positive law offers a clear legal framework, while fiqh provides a moral and religious foundation that supports the social and ethical dimensions of child protection. Integrating these perspectives can lead to a more holistic approach, combining legal rigor with religious principles to safeguard children's rights. This collaboration may strengthen child protection strategies by being more adaptive to socio-cultural contexts, offering a comprehensive solution to combat child abuse and ensure children's rights are effectively protected.